2001
DOI: 10.1177/194589240101500509
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Repair of Cerebrospinal Fluid Rhinorrhea: Learning from Our Failures

Abstract: Endoscopic repair of cerebrospinal fluid (CSF) rhinorrhea is becoming a common procedure. The purpose of this study was to perform a literature analysis centering cases of treatment failure and to review our 31 cases with a 1-year minimum follow-up. An extensive search of the literature was conducted, which focused on success rate, follow-up, diagnostic techniques, graft material used, failure rate, and comments on failures. A retrospective analysis of our 31 patients was carried out, and all cases were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 13 publications
4
53
0
5
Order By: Relevance
“…3,[5][6][7]18) In this manner, even limited incisions to the abdomen or leg to harvest fascia lata or fat tissue can be avoided, as previous reconstructions have generally been performed using abdominal fat or fascia lata. 1,5,6,9,18) Nevertheless, no consensus has yet been established regarding the material or combination of materials and methods that can be considered the optimal remedy for repairing osteodural defects, with each option providing a similar number of pros and cons. The choice of adequate technique and materials to be used should therefore be addressed in each case based on the experience of the surgeon and the features of the osteodural defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[5][6][7]18) In this manner, even limited incisions to the abdomen or leg to harvest fascia lata or fat tissue can be avoided, as previous reconstructions have generally been performed using abdominal fat or fascia lata. 1,5,6,9,18) Nevertheless, no consensus has yet been established regarding the material or combination of materials and methods that can be considered the optimal remedy for repairing osteodural defects, with each option providing a similar number of pros and cons. The choice of adequate technique and materials to be used should therefore be addressed in each case based on the experience of the surgeon and the features of the osteodural defect.…”
Section: Discussionmentioning
confidence: 99%
“…18,20,22) The widespread application of endoscopic endonasal techniques extending beyond the sellar region 2,4,11) has recently led neurosurgeons and otorhinolaryngological surgeons to advocate this technique as a possible treatment option for CSF leaks. 5,6,15,18,22) We report a case of traumatic ethmoidal leak that was successfully treated using a purely endoscopic endonasal method.…”
Section: Introductionmentioning
confidence: 99%
“…72,80 Various authors have successfully used different types of autologous and nonautologous grafts, such as a mucoperiosteal flap from the middle turbinate or septum or mucoperichondrial, osseous, cartilaginous, fat, muscular fascia, middle turbinate, or septum pedunculated graft, or any combination of these grafts. 1,3,11,13,15,22,[24][25][26]28,35,47,51,55,56,64,65,67,77,79,90,101,108 Another widely discussed issue in endoscopic transnasal repair is whether the grafts used for repair should be placed above (inlay) or beneath (onlay) the skull base defects. In a meta-analysis, Hegazy et al 53 found that both techniques yielded similar results.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Several Graft materials can be used; cartilage, bone, mucoperichondrium, septal mucosa, turbinate, fascia, abdominal fat, conchal cartilage, free tissue, pedicle tissue or composite grafts. The uses of the various types of graft materials do not seem to alter the outcome [4, 45,46,47]. Different ways of applying the graft; Bathplug see ( Figure 3) where a fat plug with a specifically secured vicryl suture into the intradural space [48], Composite mucochondrial flap, for larger defects [49], Middle turbinate, composite bone/mucosa, for moderate and large defects [42], Inferior turbinate graft for defects > 2 cm [50].…”
Section: Preparationsmentioning
confidence: 99%
“…Several Graft materials can be used; cartilage, bone, mucoperichondrium, septal mucosa, turbinate, fascia, abdominal fat, conchal cartilage, free tissue, pedicle tissue or composite grafts. The uses of the various types of graft materials do not seem to alter the outcome [4,45,46,47]. Different ways of applying the graft; Bathplug see ( Figure 3) …”
mentioning
confidence: 99%